(untitled) (Journal of Pedagogical Inventions and Practices, 2021)
The purpose of working on this topic is to identify the theoretical foundations and methods of technology for the development of children’s motor skills in preschool education on the basis of the use of movement games as a means of physical education. Although some studies have focused on the targeted development of physical activity skills and mental processes in preschool children based on movement games, they have not been discussed in detail.